2009
DOI: 10.1161/strokeaha.109.565119
|View full text |Cite|
|
Sign up to set email alerts
|

Ancrod in Acute Ischemic Stroke

Abstract: Background and Purpose-Previous studies of multiple-day dosing with the defibrinogenating agent, ancrod, in acute ischemic stroke yielded conflicting results but suggested that a brief dosing regimen might improve efficacy and safety. The Ancrod Stroke Program was designed to test this concept in subjects beginning ancrod or placebo within 6 hours of the onset of acute ischemic stroke. Methods-Five hundred subjects with acute ischemic stroke who could begin receiving study material within 6 hours of symptom on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
33
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(34 citation statements)
references
References 17 publications
0
33
0
1
Order By: Relevance
“…A follow-up clinical trial, in which 500 subjects with AIS were randomized within 6 hours of symptoms to ancrod at 0.167 IU/kg IV per hour vs placebo for 2 to 3 hours, showed no difference in clinical outcome between the 2 groups. 49 A favorable functional outcome at 39.6% in the treatment arm vs 37.2% ( p ϭ 0.47) was found.…”
mentioning
confidence: 84%
“…A follow-up clinical trial, in which 500 subjects with AIS were randomized within 6 hours of symptoms to ancrod at 0.167 IU/kg IV per hour vs placebo for 2 to 3 hours, showed no difference in clinical outcome between the 2 groups. 49 A favorable functional outcome at 39.6% in the treatment arm vs 37.2% ( p ϭ 0.47) was found.…”
mentioning
confidence: 84%
“…They are characterized by longer half life and higher fibrin specificity and, hence, a possibly lower risk of bleeding. However, recent clinical trials were disappointing (38). Therefore, in order to find effective treatment options in stroke, we need to identify novel mechanism-based targets.…”
mentioning
confidence: 99%
“…The tPA duteplase [54] is used primarily in Japan; the use of streptokinase is generally avoided after evidence of an unfavourable benefit/ safety balance [55][56][57]. Recent trials of desmoteplase [58] and ancrod [59] have not indicated a benefit.…”
Section: Reperfusion To Treat Ischaemic Strokementioning
confidence: 99%